Arteriovenous access surgery : ensuring adequate vascular access for hemodialysis - Scholz, Hans (Springer Berlin Heidelberg Imprint: Springer, 2015)
Owing to demographic trends and medical progress, the number of patients requiring renal replacement therapy is increasing steadily. Longer survival on hemodialysis also means that surgeons have to face more complex and challenging situations regarding life-sustaining access vessels.   This book offers a comprehensive overview of up-to-date knowledge on vascular access surgery. Written by a senior author with more than 30 years of experience and by expert contributors, it covers both surgical and theoretical aspects. The author shares his expertise in a hands-on approach, and presents his views on the difficulties that every clinician may encounter.   The various options for vascular access creation are carefully reviewed. Detailed descriptions and numerous accompanying illustrations of AV fistulas, AV prosthetic grafts, and arterioarterial grafts are provided, and a chapter is also devoted to the use of central venous catheters. Potential complications and their management are explained in depth, and advice is offered on how to deal with special patient groups requiring extra attention. Separate chapters on fluid dynamics (drawing on the author's own research) and vascular pathology cater for the needs of those with a particular interest in the pathophysiological principles.